IGlarLixi versus premixed insulin initiation in adults with type 2 diabetes advancing from basal insulin therapy: The SoliComplex real‐world study. Issue 5 (28th February 2023) - Lajara, Rosemarie; Heller, Caroline; Pantalone, Kevin M.; Lew, Elisheva; Li, Xuan; Dex, Terry; Kilpatrick, Catherine Rachel
Abstract: Aim: To compare outcomes in adults with type 2 diabetes (T2D) suboptimally controlled with basal insulin who initiated treatment with iGlarLixi or premixed insulin. Methods: This retrospective real‐world analysis was conducted using data from adults (age ≥ 18 years) with T2D in the US Optum Clinformatics database who had previously received basal insulin and newly initiated iGlarLixi or premixed insulin. Cohorts were propensity‐score matched on baseline characteristics using a greedy nearest neighbour‐matching algorithm, and outcomes were assessed at 12 months. Subgroup analyses were performed for those aged 65 years or older and those with a baseline HbA1c of 9% or higher. The primary endpoint was treatment persistence in the overall population. Secondary endpoints were treatment adherence, healthcare resource utilization (HRU), costs, hypoglycaemia events and change in HbA1c from baseline. Results: Each cohort comprised 834 participants. In the overall population, treatment persistence at 12 months was statistically significantly higher for iGlarLixi versus premixed insulin: 42.5% versus 39.1%; hazard ratio 0.88; 95% confidence interval 0.778‐0.998; P  = .0465. Adherence and HbA1c reduction were similar between groups, whereas hypoglycaemia events, HRU and costs were numerically lower for iGlarLixi. Outcomes in both the age 65 years or older subgroup and in those with an HbA1c of 9% or higher were consistent with those for the overall population. Conclusions: In this observational study in people with T2D suboptimally controlled on basal insulin, once‐daily iGlarLixi was an effective treatment alternative to premixed insulin with significantly higher treatment persistence, similar adherence and HbA1c reduction, and numerically lower hypoglycaemia events, HRU and costs, regardless of age or baseline HbA1c.